The Role of the Nongovernmental Organizations in Rural Development Induction in North Kordofan State, Sudan - E.Maruod, Maruod; Suliman, Gaafar B.; Elzain, Elzubair E.; Abdalla, Mohammed Y.; Marouf, Attika M. E. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
The study aimed to evaluate the contributions of voluntary organizations on rural development in North Kordofan State. Research hypothesis were voluntary organizations played a positive role in creating rural development in Sheikan locality, and enhance the sustainability of the development. The Research pursued the analytical descriptive statistic methodology primary data were collected through the field survey that targeted random samples consisting of (192) households. The data were analyzed using descriptive statistical analysis. The secondary resources include references, researches, workshops papers, projects reports, periodicals and the internet. The study findings were: the voluntary organizations interventions effects in the study area played a positive role in the developmental process in the fields of health, basic education situation and availability of drinking water for both human and livestock by 98.4, 96.4 and 99.9% for each respectively. 95.8% of the total targeted households were satisfied with the type of services (health, education and water) in Sheikan locality demonstrating that the organizations had succeeded in providing services and better livelihood. The study recommends comprehensive communities engagement and full participation in the development planning priorities, implementation and monitoring, supporting the implementation of programs and projects that leads to stability and social cohesion and reduce conflicts over resources, Sheikan locality should work to develop a comprehensive plan on education obstacles , health care deficiency , availability of healthy water, and livelihood of rural communities.